Anthropogenic selection enhances cancer evolution in Tasmanian devil tumours. (6th November 2013) - Ujvari, Beata; Pearse, Anne‐Maree; Swift, Kate; Hodson, Pamela; Hua, Bobby; Pyecroft, Stephen; Taylor, Robyn; Hamede, Rodrigo; Jones, Menna; Belov, Katherine; Madsen, Thomas
Abstract The Tasmanian Devil Facial Tumour Disease (DFTD) provides a unique opportunity to elucidate the long‐term effects of natural and anthropogenic selection on cancer evolution. Since first observed in 1996, this transmissible cancer has caused local population declines by >90%. So far, four chromosomal DFTD variants (strains) have been described and karyotypic analyses of 253 tumours showed higher levels of tetraploidy in the oldest strain. We propose that increased ploidy in the oldest strain may have evolved in response to effects of genomic decay observed in asexually reproducing organisms. In this study, we focus on the evolutionary response of DFTD to a disease suppression trial. Tumours collected from devils subjected to the removal programme showed accelerated temporal evolution of tetraploidy compared with tumours from other populations where no increase in tetraploid tumours were observed. As ploidy significantly reduces tumour growth rate, we suggest that the disease suppression trial resulted in selection favouring slower growing tumours mediated by an increased level of tetraploidy. Our study reveals that DFTD has the capacity to rapidly respond to novel selective regimes and that disease eradication may result in novel tumour adaptations, which may further imperil the long‐term survival of the world's largest carnivorous marsupial.